Diagnostic application of kidney allograft‐derived absolute cell‐free DNA levels during transplant dysfunction. Issue 4 (9th November 2018) - Whitlam, John B.; Ling, Ling; Skene, Alison; Kanellis, John; Ierino, Francseco L.; Slater, Howard R.; Bruno, Damien L.; Power, David A.
Abstract : Graft‐derived cell‐free DNA (donor‐derived cell‐free DNA) is an emerging marker of kidney allograft injury. Studies examining the clinical validity of this biomarker have previously used the graft fraction, or proportion of total cell‐free DNA that is graft‐derived. The present study evaluated the diagnostic validity of absolute measurements of graft‐derived cell‐free DNA, as well as calculated graft fraction, for the diagnosis of graft dysfunction. Plasma graft‐derived cell‐free DNA, total cell‐free DNA, and graft fraction were correlated with biopsy diagnosis as well as individual Banff scores. Sixty‐one samples were included in the analysis. For the diagnosis of antibody mediated rejection, the receiver‐operator characteristic area under the curves of graft‐derived cell‐free DNA and graft fraction were 0.91 (95% CI 0.82‐0.98) and 0.89 (95% CI 0.79‐0.98), respectively. Both measures did not diagnose borderline or type 1A cellular mediated rejection. Graft fraction was associated with a broader range of Banff lesions, including lesions associated with cellular mediated rejection, while graft‐derived cell‐free DNA appeared more specific for antibody mediated rejection. Limitations of this study include a small sample size and lack of a validation cohort. The capacity for absolute quantification, and lower barriers to implementation of this methodology recommend it for further study. Abstract : The absolute measurements of plasma graft‐derived and total cell‐derived DNA, with the relative measure of calculated graft fraction, have good diagnostic performance for antibody‐mediated rejection in kidney transplant recipients undergoing for‐cause biopsy.